Achnanthidium exiguum (Bacillariophyta): nuevas citas para localidades andinas del norte de Chile - RIVERA, PATRICIO; CRUCES, FABIOLA (Gayana Botánica, 2018)
Achnanthidium exiguum is reported for the first time from Salar de Huasco and Salar de Aguas Calientes in northern Chile. The morphological features of the species are described and illustrated with light and electron microscopy photograhs, and agree well with the type material studied by Schoeman & Archibal in 1976. The distribution of the species in Chile is also given.